Prolegomena to the Digital Legal History - S. V. Lonskaya (Теоретическая и прикладная юриспруденция, 2024)
In the article, based on formal-logical, comparative, and historical-genetic methods of cognition, the author presents their own view on the foundations of an interdisciplinary scientific field — digital legal history: its scientific status, subject, sources, goals, tasks, and methodology. Digital legal history is a part as the history of law and the digital humanities. While remaining within the disciplinary subject of legal history (history of state and law), digital legal history methodologically intersects with informatics, studying historical legal sources using digital technologies and tools. At the core of the methodology of digital legal history lies the source-oriented paradigm (phenomenological concept of cognitive history and source studies method) and specialized digital research methods, which are combined with traditional principles, approaches, and techniques of legal historical research. The article also discusses the problems of sources in historical-legal research, the circle of which expands in digital legal history and includes any carriers of historical-legal information (data). The need to develop new competencies for researchers in the field of digital legal history, and the formation of a corresponding scientific and educational environment and infrastructure are highlighted. The conclusion is drawn that digital legal history, as an interdisciplinary scientific field, is transitioning from the stage of its genesis to institutionalization.